KARAKTERISTIK PENDERITA TUBERKULOSIS PARU DEWASA RAWAT INAP DI RUMAH SAKIT UMUM DR. SOEDARSO PONTIANAK PERIODE SEPTEMBER - NOVEMBER 2010 - ., Freddy Panjaitan (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Tuberculosis (TB) become a national issue because this disease is the thirdmost deadly disease after heart disease and respiratory disease and the most deadlyinfectious disease. The aims of this study is to determine the characteristics of adultpulmonary tuberculosis patients.Methods: This research was a descriptive study using cross-sectional approach. Thisresearch was conducted in the ward dr. Soedarso General Hospital Pontianak duringSeptember to November 2010. Data collected from 45 patients that met the study criteria.Data were collected by questionnaire-based interview method.Result: The incidence of pulmonary TB was 77.8% in the reproductive age group.Pulmonary TB incidence was 60% in men and 40% in women. Educational background ofthe sample was still low with 26.7% of the sample were un-educated, 24.4% elementary,junior high 28.9%, 17.8% senior high school and only 2.2% college/university.Socioeconomic level of 84.4% sample was still low with income less than Rp. 705.000,-per month. Type of pulmonary tuberculosis patients the most was new cases as much as62.2%, followed by cases of relapse of 24.4% and 13.4% of cases defaulted. Nutritionalstatus of most patients was poor, 80.0% subjects had BMI less than 18.5 kg/m2.Conclusion: Pulmonary TB is still dominated by people in reproductive age with lowsocioeconomic levels and poor nutritional status.Keywords: Pulmonary tuberculosis, Characteristics, Age, Gender, Education grade,Social economy, Type of patient, Nutritional status.